Meta-Analysis of Cell Therapy Trials for Patients With Heart Failure. Issue 8 (10th April 2015) - Fisher, Sheila A; Doree, Carolyn; Mathur, Anthony; Martin-Rendon, Enca
<x xml:space="preserve">Abstract</x> Rationale: Cell-based therapies are a promising intervention for the treatment of heart failure (HF) secondary to ischemic and nonischemic cardiomyopathy. However, the clinical efficacy of such new treatment requires further evaluation. Objective: To assess available clinical evidence on the safety and efficacy of cell-based therapies for HF. Methods and Results: Electronic databases (CENTRAL, DARE, NHSEED & HTA, PubMed, MEDLINE, EMBASE, CINAHL, LILACS, KoreaMed, PakMediNet, IndMed, and the Transfusion Evidence Library) were searched for relevant randomized controlled trials to June 2014. Trials of participants with HF and where the administration of any dose of autologous cells by any delivery route was compared with no intervention or placebo were eligible for inclusion. Primary outcomes were defined as mortality and rehospitalization as a result of HF. Secondary outcomes included performance status, quality of life, incidence of arrhythmias, brain natriuretic peptide levels, left ventricular ejection fraction, myocardial perfusion, and adverse events. Thirty-one independent trials (1521 participants) were included. The treatment significantly reduced the risk of mortality and rehospitalization caused by HF. There was a significant improvement in favor of stem cell treatment in performance status and exercise capacity, left ventricular ejection fraction, and quality of life. The treatment was also associated with a reduction of brain natriuretic peptide levels and no increase in the incidence of arrhythmias. However, there was considerable risk of performance, selection, and reporting bias among the included trials. Conclusions: This study shows evidence that autologous cell therapy may be beneficial for patients having HF, but further evidence is required.